The importance of observing the master’s hand: Action Observation Training promotes the acquisition of new musical skills - Paolini, Simone; Bazzini, Maria Chiara; Ferrari, Laura; Errante, Antonino; Fogassi, Leonardo; Rizzolatti, Giacomo; Fabbri-Destro, Maddalena; Avanzini, Pietro; Nuara, Arturo (Frontiers in Neurology, 2024)
Introduction Via mirror mechanism, motor training approaches based on the alternation of action observation and execution (i.e., Action Observation Training-AOT) promote the acquisition of motor abilities. Previous studies showed that both visual and auditory stimuli may elicit a common motor representation of music-related gestures; however, the potentialities of AOT for the acquisition of musical skills are still underexplored. Methods Twenty-one music-naïve participants underwent two blocks of training: AOT and Key-light Observation Training (KOT). AOT consisted of the observation of a melodic sequence played on a keyboard with the right hand by an expert model, followed by participant’s imitation. Observation and execution were repeated six consecutive times (T1–T6). KOT followed the same procedure, except for the visual content of the stimulus, depicting the sequential highlighting of the piano keys corresponding to the melody. The rate of correct notes (C), the trainee-model similarity of key-pressure strength (S), and the trainee-model consistency of note duration (R) were collected across T1–T6. Results Both AOT and KOT improved musical performance. Noteworthy, AOT showed a higher learning magnitude relative to KOT in terms of C and S. Discussion Action Observation Training promotes the acquisition of key elements of melodic sequences, encompassing not only the accurate sequencing of notes but also their expressive characteristics, such as key-pressure dynamics. The convergence of listening and observation of actions onto a shared motor representation not only explains several pedagogical approaches applied in all musical cultures worldwide, but also enhances the potential efficacy of current procedures for music training.